2010
DOI: 10.1186/1471-2407-10-424
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjuvant chemotherapy for gliomatosis cerebri

Abstract: BackgroundGliomatosis cerebri (GC) is characterized by a diffuse infiltration of tumor cells throughout CNS, however, few details are available about the chemotherapeutic effect on GC. The aim of this study was to investigate its clinical course and to determine the efficacy of chemotherapy for GC.MethodsBetween Jan. 1999 and Dec. 2004, 37 GC patients were diagnosed by biopsy and treated with radiotherapy in a single institution. To determine the efficacy of chemotherapy for GC, we retrospectively reviewed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
4
11
1
Order By: Relevance
“…Galectin-3 expression in glial tumor cells has been reported to be related to infiltrative cell motility away from hypoxic regions (27). Our molecular and immunohistochemical observations are interesting in the context of previously published data, as GC has been considered a lesion of intermediate malignancy in the progression of diffuse glioma to GBMs, and the progression of GC is mediated by tumor stem cells (20). As GC shares characteristics with neural stem cells, GC may show migratory behavior, diversity of progeny and proliferative potential (20).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Galectin-3 expression in glial tumor cells has been reported to be related to infiltrative cell motility away from hypoxic regions (27). Our molecular and immunohistochemical observations are interesting in the context of previously published data, as GC has been considered a lesion of intermediate malignancy in the progression of diffuse glioma to GBMs, and the progression of GC is mediated by tumor stem cells (20). As GC shares characteristics with neural stem cells, GC may show migratory behavior, diversity of progeny and proliferative potential (20).…”
Section: Discussionsupporting
confidence: 72%
“…Our molecular and immunohistochemical observations are interesting in the context of previously published data, as GC has been considered a lesion of intermediate malignancy in the progression of diffuse glioma to GBMs, and the progression of GC is mediated by tumor stem cells . As GC shares characteristics with neural stem cells, GC may show migratory behavior, diversity of progeny and proliferative potential . Herrlinger et al have shown that 52.2% GCs show GBM‐IDHwt‐associated methylation profile, suggesting a close relationship between GC and GBM at the molecular level.…”
Section: Discussionsupporting
confidence: 68%
“…In the future, more data about patients who received concurrent radiation/temozolomide followed by adjuvant temozolomide (as is now standard for glioblastoma multiforme [12]) may become available. Others have reported benefit for chemotherapy in gliomatosis, including temozolomide [42-46] and nitrosoureas (especially for tumors with an oligodendroglial component) [47]. Thus, our series does not definitively rule out a role for chemotherapy in gliomatosis cerebri.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, there is no consensus on the best approach for affected patients. In fact, there was no agreement among experts present in Paris about the real impact that chemotherapy or radiotherapy may have on this disease …”
Section: Is There a “Standard Of Care”?mentioning
confidence: 99%
“…In fact, there was no agreement among experts present in Paris about the real impact that chemotherapy or radiotherapy may have on this disease. [23][24][25][26][27] After confirming the diagnosis of GC based on imaging and histologic review, the panel of experts recommended the administration of upfront "institutional" chemotherapy used for HGG. Even though a few trials have attempted to establish the best chemotherapy approach for GC, there is insufficient data to recommend a specific combination.…”
Section: Is There a "Standard Of Care"?mentioning
confidence: 99%